Water Availability and water balance in Erbil Governorate - Waleed AI-Rijabo; Sardar Kareem (College of Education for Pure Sciences, 2006)
Water balance parameters were studied in four locations in Erbil Governorate which are Soran, Shaqalawa, Einkawa and ErbiJ. The mean monthly climatic parameters were taken for the different locations for the periods (2001 - 2004 ) to Soran, Shaqlawa, Einkawa according to the availability of data. For Erbil location, the climatic data was taken for the period (1992 - 2004). Water balance parameters were found during the Water Surplus Periods and water Deficit Periods . Some climatic Indexes were also found for the four locations. The evaluation of the climate in the four locations was found according to Cilianinov and Brown & Cocheme classifications